Can erythropoietin be used to prevent brain damage in cerebral malaria? - Casals-Pascual, C; Idro, R; Picot, S; Roberts, D; Newton, C (2009)
Erythropoietin (Epo) modulates the survival of developing erythroid cells and the production of new erythrocytes in the bone marrow and is a key molecule in the adaptation to hypoxia and anaemia. Epo receptors have been found to be widely expressed on non-haematopoietic cells, and Epo has been shown to have diverse actions (in particular, preventing ischaemic damage to tissues of the central nervous system). Recently, Epo has been shown to improve the outcome in a murine model of malaria, and high plasma levels of Epo in children with cerebral malaria were associated with a better outcome. Here, we review the biological importance of Epo, its mechanisms of action and the rationale for the proposed use of Epo as an adjunct treatment in cerebral malaria.